Cd(II) adsorption from aqueous solution by activated carbon from sugar beet pulp impregnated with phosphoric acid - Özer, Ahmet; Tümen, Fikret (My University, 2003)
The adsorption of Cd(II) ions from aqueous solutions onto activated carbon obtained by carbonising sugar beet pulp impregnated with 30% phosphoric acid was studied. By increasing the temperature of carbonisation, the removal efficiency of Cd(II) ions increased. The maximum removal (95.8%) was attained by activated carbon samples obtained by carbonising acid-impregnated sugar beet pulp at 500°C for 90 min. The removal efficiency of Cd(II) ions is, to a large extent, dependent on pH of medium. The results of experiments carried out at various temperatures were applied to Langmuir and Freundlich isotherm equations. The values of Langmuir constant (qmax) at 20°C were calculated as 68.03, 71.99 and 72.99 mg/g for activated carbons obtained at 300, 400 and 500°C, respectively. The adsorption process was found to be exothermic and Langmuir isotherm data were evaluated to determine the thermodynamic parameters for the adsorption process. It was found that the values of qmax and Kf decreased with increasing temperature. The data are better fitted by the second-order kinetic model as compared to first-order kinetic model.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Sugar beet pulp; Activated carbon; Cd(II) ions removal; Phosphoric acid